Faultlines: Writings on conflict and resolution (Vol.20) - Gill,K.P.S. (Ed.); Sahni,Ajai (Ed.) (New Delhi, 2011)
South Asia has seen astonishing and contradictory developments over the past dramatic year, with some insurgencies collapsing, while others waned. Despite tremendous gains, however, there is little room for complacency. While individual movements have faded, or even disappeared, others have strengthened. Terrorist formations have constantly reinvented themselves within a long-war framework; but, with rare exception, Jittle coherence has marked the national, regional and global responses to these complex threats. Crucially, the complex dynamic, which has made South Asia one of the most volatile regions in the world, has not undergone any significant structural transformation. Faultlines seeks to understand this dynamic, its underlying structures, and patterns of response.
Keywords: Social conflict